Apolipoprotein E ε4 allele decreases functional connectivity in Alzheimer's disease as measured by EEG coherence. Issue 1 (1st July 1997) - Jelic, Vesna; Julin, Per; Shigeta, Masahiro; Nordberg, Agneta; Lannfelt, Lars; Winblad, Bengt; Wahlund, Lars-Olof
Abstract : OBJECTIVES: The ε4 allele of apolipoprotein E (APOE) represents a major biological risk factor for late onset Alzheimer's disease. However, it is still not known whether the APOE genotype affects the progression of the disease, assessed by different functional methods. METHODS: The study sample included 41 patients with probable Alzheimer's disease. Subjects had similar severity of disease, age of onset, and duration of illness, and were subcategorised according to their APOE genotypes: 17 with no ε4 allele, 14 with one ε4 allele, and 10 with two ε4 alleles. The control group consisted of 18 healthy subjects comparable with the patients in age and education. Analysed quantitive EEG (qEEG) variables were the ratio of alpha and theta absolute power and EEG coherence in alpha frequency band, representing major cortical association pathways. RESULTS: There was pronounced EEG slowing in all three patient subgroups compared with the controls for the alpha/theta ratio, but there was no significant difference across the patient subgroups. Patients homozygous for the APOE ε4 allele had reduced right and left temporoparietal, right temporofrontal, and left occipitoparietal coherence. Patients without and with one ε4 allele showed an overlap between the control group and group with two ε4 alleles in coherence measures. CONCLUSIONS: APOE ε4 does not influence EEG slowing, an index which reflects severity of the disease in patients with Alzheimer's disease, but seems to be associated with selective decreases in functional connectivity as assessed by EEG coherence. This finding might be of clinical importance when considering different pathogenetic mechanisms.